Synthesis Of carbon nano-alumina framework for efficient pollutants adsorption from water and optimization via response surface methodology - Asmaly, Hamza A.; Kabbashi, Nassereldeen Ahmed; Al-Khatib, Ma'an Fahmi Rashid; Alam, Md Zahangir; Nayer, Sidra (IGSCONG’24, 2024)
The primary objective of this study was to evaluate the effectiveness of a new novel adsorbent synthesized from carbon nanotubes and carbon nanofibers integrated with alumina in purifying water contaminated with organic (2-Nitrophenol) and inorganic (Chromium III) pollutants. The alumina impregnation technique was optimized to enhance the adsorption efficiency of the nano carbon-alumina framework for these specific contaminants, and optimal adsorption conditions were identified using a central composite design approach. To comprehensively understand the composition, structure, and functional properties of the synthesized adsorbent, several analytical techniques were employed, crucial for improving its pollutant adsorption performance. The alumina content in the adsorbents was verified and quantified using Energy Dispersive X-ray (EDX) analysis, which provided a detailed quantitative assessment of alumina distribution within the adsorbent, confirming successful impregnation. Scanning Electron Microscopy (SEM) examined the morphological characteristics of the modified adsorbent, revealing surface features and morphological changes due to alumina modification, and highlighting improvements in texture and surface area essential for effective adsorption. Fourier Transform Infrared Spectroscopy (FTIR) identified the functional groups associated with aluminum oxide, ensuring its proper integration into the carbon nano adsorbent matrix. Brunauer-Emmett-Teller (BET) measurements highlighted the impact of aluminum ratios on the surface area of the modified adsorbents, with an 18% aluminum ratio resulting in a surface area of 176 m²/g, decreasing to 125 m²/g and 110 m²/g for 20% and 22% aluminum ratios, respectively.These combined analyses provided a thorough understanding of the modified adsorbent’s properties, crucial for optimizing its pollutant adsorption efficiency. The highest removal efficiency for 2-Nitrophenol and Chromium (III) was achieved with the carbon nano adsorbent-alumina at an 18% alumina impregnation ratio, following 3 hours of ultrasonication and calcination at 300°C, yielding adsorption capacities of 82.02 mg/g for 2-Nitrophenol and 96.57 mg/g for Chromium (III). The predicted adsorption capacities were 83.154 mg/g for 2-Nitrophenol and 97.80 mg/g for Chromium (III), closely matching the observed values, while validation studies showed actual adsorption capacities of 86.79 mg/g for 2-Nitrophenol and 99.79 mg/g for Chromium (III), with an acceptable error margin of about 4.5% for 2-Nitrophenol and 2% for Chromium (III).The optimized synthesis of the carbon nano-alumina framework significantly enhances its pollutant removal capabilities, particularly for purifying wastewater by extracting both organic and heavy metal contaminants, demonstrating the potential of using such modified adsorbents for effective water purification.